Asphalt-based porous carbon material, preparation method and application thereof, and battery

Through the preparation method of asphalt-based porous carbon materials, the problem of difficult balance between porous carbon materials and conductivity is solved, and porous carbon materials with high conductivity and appropriate porous structure are achieved, which improves the electrochemical performance of the battery.

CN119774587AActive Publication Date: 2025-04-08SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411998037.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

Smart Images

  • Figure CN119774587A_ABST
    Figure CN119774587A_ABST
Patent Text Reader

Abstract

The invention discloses an asphalt-based porous carbon material, a preparation method and application thereof, and a battery. The preparation method comprises the following steps: S1, mixing modulated asphalt with alkali, and then heating for preheating to obtain a first precursor; the modified asphalt comprises 15 to 60 wt% of an alpha component, 15 to 60 wt% of a beta component and 5 to 40 wt% of a gamma component. S2, continuously heating the first precursor to perform first carbonization to obtain a second precursor; and S3, continuously heating the second precursor for secondary carbonization to obtain the asphalt-based porous carbon material. A battery prepared from the asphalt-based porous carbon material is excellent in electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a pitch-based porous carbon material and a preparation method, application and battery thereof. Background Art

[0002] With the rapid development of electric vehicles and renewable energy, the demand for high-performance lithium-ion batteries continues to increase. For the negative electrode, the currently widely used negative electrode materials are various carbon materials based on graphite, and their theoretical capacity is only 372mAh / g. In actual application, it is close to its theoretical capacity and it is difficult to meet higher capacity requirements. Therefore, the research on high specific capacity negative electrode active materials has become a general trend. Among them, the theoretical capacity of silicon materials is much higher than that of graphite carbon materials, which can reach 4200mAh / g, and the resources are relatively abundant, making it the main choice for the next generation of new negative electrode materials.

[0003] However, the silicon-carbon negative electrode has a serious expansion problem. The volume expansion of silicon material during the charge and discharge process is close to 300%, which will cause a significant decrease in the overall performance of the battery. Faced with the challenges of capacity attenuation and poor cycle stability, solving this defect of silicon material is a topic that is being studied at home and abroad. CVD deposition of silicon-carbon has been a technical direction that has received a lot of attention and has good performance in recent years.

[0004] Porous carbon materials have advantages such as high specific surface area, excellent conductivity and good mechanical stability. They are also key materials for CVD deposition of silicon carbon. They must have high performance and feasibility for large-scale production. Porous carbon materials can be prepared from cheap natural resources, which helps to reduce the cost of battery manufacturing, thereby achieving sustainable development and reducing dependence on limited resources. The pore size, specific surface area and pore volume of porous carbon have an important influence on the structure and performance of CVD silicon anode. As a substrate material, porous carbon is a good carrier for silicon nucleation and growth. Its developed pore structure is conducive to accommodating the volume expansion of silicon, thereby improving the electrochemical activity of the electrode. At the same time, the conductivity and thermal stability of porous carbon are directly related to the overall performance of the silicon anode.

[0005] The conductivity of silicon itself in silicon carbon is poor, and the construction of a conductive network mainly relies on a porous carbon skeleton and a conductive coating formed by depositing conductive substances (carbon, gold, silver, copper, aluminum, iron, etc.). As in patent application CN202311507560.1, improving conductivity basically relies on the existing carbon skeleton conductivity + carbon deposition layer. Patent application CN202311439082.5 adopts a method of heteroatom improvement of the carbon skeleton. Even if some methods use asphalt as a raw material to prepare porous carbon, such as patent application CN202310054027.8, insufficient attention is paid to the influence of the component composition of the asphalt itself on the conductivity of porous carbon, and it is impossible to further improve the conductivity of porous carbon while maintaining the performance of porous carbon. Therefore, it is necessary to pay attention to the influence of the component composition of the porous carbon precursor on the performance of the porous carbon skeleton.

[0006] At present, the main method to improve the conductive properties of CVD silicon carbon is to coat the surface of the deposited nano-Si with conductive materials such as carbon, gold, silver and copper while maintaining a certain porous structure, capture the silicon particles into a rigid matrix, and provide space through structures such as core-shell and yolk-shell to adapt to volume changes, etc., which can also improve the conductivity of Si. The method for improving the conductivity of porous carbon skeletons is more to dope and modify the carbon skeleton materials, such as doping with heteroatoms such as N / S, or doping with metal atoms such as Au / Ag / Al / Cu / Fe on the carbon skeleton, or using a conductive deposition layer. If the pores are too rich, the porous carbon skeleton material will be too brittle, the carbon wall will be thin, and the conductivity will be poor, which will increase the resistance of silicon carbon to a certain extent. Therefore, it is necessary to find a suitable balance between pore structure and conductivity. Summary of the invention

[0007] In order to solve the problem of the difficulty in balancing the pore structure and conductivity of porous carbon materials, the present invention proposes an asphalt-based porous carbon material and its preparation method, application and battery. The asphalt-based porous carbon material can meet the requirements of the inherent electrode resistance and charge transfer resistance of the carbon material caused by the expansion of silicon materials during the charge and discharge cycle, and the battery prepared by using the asphalt-based porous carbon material has excellent electrochemical performance.

[0008] The present invention adopts the following technical solutions to solve the above technical problems:

[0009] The present invention provides a method for preparing a pitch-based porous carbon material, which comprises the following steps:

[0010] S1, mixing a modulated asphalt with an alkali and heating it for preheating to obtain a first precursor; the modulated asphalt comprises 20-40wt% of an α component, 20-60wt% of a β component and 10-50wt% of a γ component;

[0011] S2, continuing to heat the first precursor to perform a first carbonization to obtain a second precursor;

[0012] S3. Continue to heat the second precursor to perform a second carbonization to obtain a pitch-based porous carbon material.

[0013] In a preferred embodiment, before step S1, the step S0 is further included, mixing the asphalt raw material with the washing oil to obtain the modulated asphalt. The mass ratio of the asphalt raw material to the washing oil can be (0.5-6):1, for example, 1.2:1, 0.5:1, 4:1.

[0014] In the present invention, the softening point of the prepared asphalt in step S1 may be 80-120°C, for example, 95°C.

[0015] In the present invention, the modulated asphalt in step S1 may contain 30wt% of α component, 38wt% of β component, and 32wt% of γ component; or, the modulated asphalt may contain 29wt% of α component, 27wt% of β component, and 44wt% of γ component; or, the modulated asphalt may contain 31wt% of α component, 49wt% of β component, and 20wt% of γ component.

[0016] The α component of step S1 is quinoline insoluble, the β component is toluene insoluble quinoline soluble, and the γ component is toluene soluble. Wherein, quinoline insoluble refers to the component in asphalt or tar that is insoluble in quinoline. Toluene insoluble quinoline soluble refers to the component in asphalt or tar that cannot be dissolved by toluene but can be dissolved by quinoline. Toluene soluble refers to the component in asphalt or tar that can be dissolved in toluene.

[0017] Among them, the wash oil is the 230-300°C fraction cut during tar distillation, which is generally a yellowish brown to brown oily liquid, rich in organic chemical raw materials such as quinoline, isoquinoline, indole, α-methylnaphthalene, β-methylnaphthalene, biphenyl, dimethylnaphthalene, acenaphthene, dibenzofuran and fluorene, with the highest content of naphthalene compounds.

[0018] The asphalt raw material may be a conventional asphalt raw material in the art, including one or more of petroleum asphalt, coal asphalt and natural asphalt, such as coal asphalt.

[0019] In step S1, the softening point of the asphalt raw material may be 55-150°C, preferably 100-120°C, such as 105°C.

[0020] In step S1, the asphalt raw material comprises: 20-50wt% (e.g. 32wt%) of α component, 10-60wt% (e.g. 58wt%) of β component, 5-70wt% (e.g. 10wt%) of γ component, wherein wt% refers to the mass proportion of a substance in the mixture.

[0021] In step S1, the average relative molecular mass of the modulated asphalt may be 1000-1800, for example, 1000, 1400, 1800.

[0022] In step S1, the C / H of the prepared asphalt may be 1.25-2.0, preferably 1.35-1.85, such as 1.48, 1.57, 1.35.

[0023] In the present invention, in step S1, the base can be a porogen commonly used in the art. Preferably, the base is one or more of potassium hydroxide, potassium carbonate, potassium chloride, sodium carbonate, sodium chloride, zinc chloride, zinc carbonate and phosphoric acid, for example, potassium hydroxide.

[0024] In step S1, the prepared asphalt may be in a granular form, and the D 50 Preferably, it is 6-18 μm, more preferably, it is 8-12 μm, for example, 10 μm.

[0025] In the present invention, preferably, in step S1, the mass ratio of the modulated asphalt to the alkali is 1:(1-5), for example, 1:1 or 1:4.

[0026] In the present invention, the pre-heating temperature in step S1 is a conventional heating temperature in the art. Preferably, the heating temperature in step S1 may be 90-140°C, preferably 110-130°C, for example 125°C. The heating rate in step S1 may be 0.5-20°C / min, for example 2°C / min.

[0027] In a specific implementation scheme, the specific steps of preheating in step S1 are: heating the powder obtained by mixing the above-mentioned modulated asphalt and alkali to a heating temperature and then keeping it warm, and then introducing a non-reactive gas after ensuring that the asphalt is completely melted into a liquid state.

[0028] Preferably, the non-reactive gas is one or more of nitrogen, helium and argon. The gas flow rate of the non-reactive gas may be 0.05-60 L / min, preferably 0.05-1 L / min, such as 0.2 L / min.

[0029] The insulation time may be 0.2-2 hours, preferably 0.5-1.5 hours, for example 30 minutes.

[0030] In the present invention, in step S2, the temperature of the first carbonization may be 200-600°C, preferably 400-500°C, such as 450°C.

[0031] In step S2, the heating rate may be 0.5-20°C / min, for example 3°C / min.

[0032] In a specific implementation scheme, the specific steps of the first carbonization in step S2 are: introducing a non-reactive gas into the first precursor at a pre-heated temperature, and continuing to heat the first precursor to a first carbonization temperature and keeping the temperature.

[0033] Wherein, the non-reactive gas in step S2 is one or more of nitrogen, helium and argon. Wherein, the gas flow rate of the non-reactive gas in step S2 can be 0.05-60 L / min, for example 0.2 L / min.

[0034] The insulation time in step S2 may be 1-6 hours, for example 1 hour.

[0035] In a specific implementation scheme, the specific steps of the second carbonization in step S3 are: maintaining a non-reactive gas atmosphere, continuing to heat to the temperature of the second carbonization and keeping warm, cooling to room temperature after keeping warm, taking out, acid washing 3 times, washing with water 3 times, and then drying.

[0036] Wherein, the non-reactive gas in step S3 includes but is not limited to one or more of nitrogen, helium and argon.

[0037] Wherein, the gas flow rate of the non-reactive gas in step S3 may be 0.05-60 L / min, for example 0.15 L / min.

[0038] The acid solution used for pickling is a conventional acid solution in the art. Preferably, the acid solution can be one or more of hydrochloric acid solution, phosphoric acid solution, nitric acid solution, sulfuric acid solution, acetic acid solution, and formic acid solution, such as hydrochloric acid solution.

[0039] The concentration of the acidic solution may be 0.5-6 mol / L, for example 3 mol / L.

[0040] The stirring time of the pickling may be 1 to 10 hours, preferably 2 to 5 hours, for example 3 hours.

[0041] Wherein, the water washing adopts deionized water washing until the solution is neutral.

[0042] In a preferred embodiment, after the washing step in step S3, a drying step may be further included.

[0043] The drying step in step S3 is a conventional drying operation in the art. The drying temperature in step S3 can be 100-120° C., for example, 105° C. The drying time in step S3 can be 2-12 hours, preferably 6-10 hours, for example, 8 hours.

[0044] In the present invention, in step S3, the temperature of the second carbonization may be 600-1400°C, for example, 700°C, 1000°C or 1300°C.

[0045] In the present invention, in step S3, the second carbonization time may be 2-8 hours, such as 2 hours, 4 hours or 7 hours.

[0046] In a specific embodiment, the heating rate of step S3 can be 0.5-20°C / min, preferably 1-10°C / min, for example 5°C / min.

[0047] In a preferred embodiment, after step S3, the method further comprises S4, spheroidizing the porous carbon material.

[0048] The spheroidization treatment takes 10-60 minutes, preferably 20-40 minutes, for example 30 minutes. The spheroidization treatment is carried out in conventional equipment in the art, for example, in a shaping machine.

[0049] Preferably, the rotation speed of the shaping machine is 20-70 rpm, preferably 40-60 rpm, for example 50 rpm.

[0050] Preferably, the D of the porous carbon material after the spheroidization treatment is 50 3-20 μm, for example 7-8 μm.

[0051] The present invention provides a pitch-based porous carbon material precursor, which is prepared by the following steps S1:

[0052] S1. Mix the modulated asphalt with alkali and heat it for pre-heating to obtain an asphalt-based porous carbon material precursor; the modulated asphalt contains 20-40wt% of α component, 20-60wt% of β component and 10-50wt% of γ component; wherein the conditions and operation of step S1 are as described above.

[0053] The present invention provides a pitch-based porous carbon material precursor, which is prepared by the following steps S1-S2:

[0054] S1, mixing a modulated asphalt with an alkali and heating it for preheating to obtain a first precursor; the modulated asphalt comprises 20-40wt% of an α component, 20-60wt% of a β component and 10-50wt% of a γ component;

[0055] S2. Continue to heat the first precursor to perform a first carbonization to obtain a pitch-based porous carbon material precursor, wherein the conditions and operation of step S1 are the same as those described above, and the conditions and operation of step S2 are the same as those described above.

[0056] The present invention provides a pitch-based porous carbon material prepared by the method for preparing the pitch-based porous carbon material.

[0057] In the present invention, the specific surface area of ​​the asphalt-based porous carbon material may be 900-2500 m 2 / g, preferably 1000-1800m 2 / g, for example 1123m 2 / g, 1543m 2 / g, 1641m 2 / g.

[0058] In the present invention, the pore size D of the pitch-based porous carbon material is 50 It may be 1-15 nm, for example, 2.146 nm, 3.176 nm, 3.209 nm, 3.653 nm, 4.641 nm, 5.278 nm, 9.017 nm or 14.45 nm.

[0059] In the present invention, the pore volume of the pitch-based porous carbon material may be 0.5-1.3 cm 3 / g, for example, 0.6436cm 3 / g, 0.6936cm 3 / g, 0.764cm 3 / g, 0.8987cm 3 / g, 0.9254cm 3 / g, 0.9423cm 3 / g, 1.034cm 3 / g or 1.278cm 3 / g.

[0060] In the present invention, the powder resistivity (20 MPa) of the pitch-based porous carbon material may be 0.04-0.16Ω*cm, for example, 0.0498Ω*cm, 0.0577Ω*cm, 0.0752Ω*cm, 0.0818Ω*cm, 0.0824Ω*cm, 0.1023Ω*cm, 0.1176Ω*cm or 0.1578Ω*cm.

[0061] The present invention provides an application of the asphalt-based porous carbon material as described above as an electrode material.

[0062] Wherein, the electrode material is preferably a negative electrode material.

[0063] The present invention also provides a battery, which comprises the above-mentioned asphalt-based porous carbon material.

[0064] In the present invention, the battery is preferably a sodium ion battery.

[0065] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0066] The reagents and raw materials used in the present invention are commercially available.

[0067] The positive and progressive effects of the present invention are:

[0068] (1) The present invention improves the conductivity of the matrix itself by adjusting the ratio of each component in the modulated asphalt. The first efficiency of the obtained battery is above 89%, and the rate at 4C is also above 75%.

[0069] (2) The present invention can design the resistivity of the porous carbon skeleton according to the silicon content by adjusting the β component of the asphalt, thereby meeting the requirements of the inherent electrode resistance and charge transfer resistance of the carbon material caused by the expansion of the silicon material during the charge and discharge cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 This is a pore size distribution diagram of the asphalt-based porous carbon material obtained in Example 1 of the present invention.

[0071] Figure 2 This is the SEM morphology of the asphalt-based porous carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0072] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0073] Coal tar pitch, with a softening point of 150°C, α component accounting for 32wt%, β component accounting for 58wt%, and γ component accounting for 10wt%, was purchased from Shandong Oriental Hualong Group.

[0074] Coal washed oil, with alpha component accounting for 27wt%, beta component accounting for 12wt%, and gamma component accounting for 61wt%, was purchased from Shandong Oriental Hualong Group.

[0075] Example 1

[0076] S0, Asphalt Mixing

[0077] Coal tar and coal washing oil are mixed in a mass ratio of 1.2:1 to obtain modulated asphalt (softening point = 95°C, average relative molecular mass 1400, C / H molar mass ratio = 1.48, α component accounts for 30wt%, β component accounts for 38wt%, and γ component accounts for 32wt%).

[0078] S1, preheating

[0079] 40g of the prepared modulated asphalt (average relative molecular mass 1400, C / H molar mass ratio 1.48) was selected and added to a stainless steel sampling barrel, and then the solid powder was mixed at a mass ratio of 1:4 between the modulated asphalt and KOH. The mixed powder was preheated to 125°C at a heating rate of 2°C / min to ensure that the asphalt was completely melted into a liquid state. After maintaining for 30 minutes, N2 gas was introduced at a flow rate of 0.2L / min to obtain the first precursor.

[0080] S2, first carbonization

[0081] On the basis of the pre-heated temperature, N2 gas was continued to be introduced into the first precursor at a flow rate of 0.2 L / min, and the temperature was continued to be increased to 450°C at a heating rate of 3°C / min and maintained at a constant temperature for 1 hour to obtain a second precursor.

[0082] S3, Second Carbonization

[0083] Maintaining a nitrogen atmosphere with a gas velocity of 0.15L / min, the carbonized material continued to be heated to 1000°C at a heating rate of 5°C / min and kept at a constant temperature for 4h, and then taken out after cooling to room temperature. Add 5wt% HCl in an amount twice the volume of the carbonized material, stir at 200rpm for 30min, centrifuge at 3000rpm / min, and then replace the acid solution with deionized water and wash it three times in the same way, and then put it into a blast oven at 110°C for 8h to obtain a pitch-based porous carbon material;

[0084] S4, spheroidization finishing

[0085] The prepared asphalt-based porous carbon material was placed in a shaping machine for spheroidization treatment at a rotation speed of 50 rpm and a treatment time of 30 min to obtain an asphalt-based porous carbon material with D50 = 7-8 μm.

[0086] Example 2

[0087] The difference between this embodiment and embodiment 1 is that coal tar and coal washing oil are mixed in a mass ratio of 0.5:1 to obtain a modulated asphalt, the softening point of the modulated asphalt = 130°C, the average relative molecular mass is 1800, the C / H molar mass ratio is 1.57, the α component accounts for 29wt%, the β component accounts for 27wt%, and the γ component accounts for 44wt%.

[0088] Example 3

[0089] The difference between this embodiment and embodiment 1 is that coal tar and coal washing oil are mixed in a mass ratio of 4:1 to obtain modulated asphalt, the softening point of the modulated asphalt = 70°C, the average relative molecular mass is 1000, the C / H molar mass ratio is 1.35, the α component accounts for 31wt%, the β component accounts for 49wt%, and the γ component accounts for 20wt%.

[0090] Example 4

[0091] The difference between this embodiment and embodiment 1 is that the mass ratio of the modulated asphalt to KOH is 1:1, and the other conditions are exactly the same as those in embodiment 1.

[0092] Example 5

[0093] The difference between this embodiment and embodiment 1 is that the second carbonization temperature is increased to 700° C. and kept constant for 2 hours, and the other conditions are exactly the same as those in embodiment 1.

[0094] Example 6

[0095] The difference between this embodiment and embodiment 1 is that the second carbonization temperature is increased to 1300° C. and kept constant for 7 hours, and the other conditions are exactly the same as those in embodiment 1.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that coal tar and coal washing oil are mixed in a mass ratio of 0.1:1 to obtain modulated asphalt, the softening point of the modulated asphalt = 40°C, the average relative molecular mass is 500, the C / H molar mass ratio is 1.03, the α component accounts for 28wt%, the γ component accounts for 56wt%, the β component accounts for 16wt%, and the other conditions are exactly the same as in Example 1.

[0098] Comparative Example 2

[0099] The difference between this comparative example and Example 1 is that KOH is not added to mix with asphalt to form holes, and other conditions are exactly the same as those in Example 1.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that the mass ratio of the modulated asphalt to KOH is 1:6, and the other conditions are exactly the same as those in Example 1.

[0102] Effect Example 1

[0103] Characterization of specific surface area and pore structure: The specific surface area and pore structure of the material were determined using an American Micromeritics fully automatic adsorption-desorption instrument. The adsorbent for the specific surface area test was nitrogen, the measurement temperature was 77K, and it was finally calculated by the BET method. The adsorbent for the micropore size test was carbon dioxide, the measurement temperature was 273K, the powder degassing temperature was 300°C, and the relative pressure range P / P0 of the test was 0-1, which was obtained by DFT model analysis.

[0104] The pore structures and electrochemical properties of Examples 1-6 and Comparative Examples 1-3 were tested according to the above method. The relevant test results are shown in Tables 1 and Figure 1 shown.

[0105] Effect Example 2

[0106] 1. Material morphology characterization: The SEM image of the hard carbon material was obtained using a ZEISS scanning electron microscope. The SEM image of the asphalt-based porous carbon material obtained in Example 1 is as follows: Figure 2 shown.

[0107] 2. D 50 :The particle size D of the asphalt-based porous carbon material was measured using Mastersize 2000 (Malvern 2000) 50 .

[0108] 3. Pore volume: The pore volume was measured using a gas adsorption-desorption tester with nitrogen as the adsorption gas, a detection temperature of 77K, and a degassing temperature of 300°C.

[0109] 4. Powder resistivity: Suzhou Jingge ST2722B powder resistivity tester is used, and the test method is as follows: 1. Grind the test sample into powder and transfer it to a four-probe powder resistivity meter; 2. Adjust the test pressure to 20MPa, read the corresponding resistivity data, repeat 3 times, and use the average resistivity data.

[0110] The above test method was used to test Examples 1-6 and Comparative Examples 1-3. The relevant test results are shown in Table 1.

[0111] Effect Example 3

[0112] Electrochemical performance test: The prepared asphalt-based porous carbon materials were taken separately, and the mass ratio of the negative electrode material to the conductive agent (SP), the binder (SBR), and the binder (CMC) was 95.5:1.5:1.5:1.5 for homogenization, and then the slurry was coated on the copper foil by the doctor blade method, and then the coated copper foil was placed in a vacuum oven at 80°C for drying for 12 hours. The dried copper foil was cut into discs with a diameter of 14 mm to make a working electrode. At room temperature, a metal lithium sheet was used as the negative electrode and the counter electrode, the above-prepared electrode was used as the working electrode, a polypropylene diaphragm was used, a 1 mol / L LiPF6 solution was used as the electrolyte, and the volume ratio of ethylene carbonate (EC): methyl pyruvate (MC): dimethyl carbonate (DMC) was 1:1:1. CR2032 button batteries were assembled in a vacuum glove box and tightly mechanically sealed. The assembled battery was left to stand at room temperature for 24 hours before the electrochemical test began, and constant current charge and discharge experiments were carried out in the LAND battery test system.

[0113] (1) Test methods for charging capacity and initial efficiency:

[0114] The test method for discharge capacity is: discharge at 0.1C constant current to 0.01V, then discharge at 0.02C to 5mV;

[0115] The test method for charging capacity is: charging to 1.5V at 0.1C constant current;

[0116] The first effect can be calculated by the following formula:

[0117] First effect = charging capacity / discharging capacity.

[0118] (2) Ratio test method:

[0119] The charge and discharge voltage window is 0-1.5V. The battery is discharged in two steps at 0.1C to 0.01V and 0.02C to 0.005V. Then it is charged to 1.5V at different charge rates of 0.1C, 1C, 2C, 3C and 4C respectively. The rate capacity retention rate is recorded as 4C / 0.1C.

[0120] Table 1

[0121]

[0122] It can be seen from Examples 1-6 of the present invention that the present invention achieves effective regulation of relevant parameters such as the pore structure and specific surface area of ​​the asphalt-based porous carbon material through the synergistic effect between the various process steps, and the sodium ion battery made of the prepared asphalt-based porous carbon material as the negative electrode material has a higher capacity and initial efficiency.

[0123] It can be seen from Examples 1-3 that the higher the β component, the larger the molecular weight of the material, the denser it is after sintering, but the smaller the pore volume and pore size, and the lower the resistivity. Conversely, the resistivity is high.

[0124] It can be seen from Examples 1 and 4 and Comparative Example 3 that the more KOH accounts for, the more pores are formed, and the proportion of micropores will also increase accordingly, but too much KOH will not only cause the negative effect of easy collapse of pores (resulting in poor initial efficiency of the battery), but also greatly increase its cost. On the contrary, insufficient pore-forming capacity affects parameters such as pore volume, pore diameter and specific surface area.

[0125] It can be seen from Examples 1 and 5-6 that the higher the carbonization temperature and the longer the carbonization time in the second carbonization stage, the higher the proportion of macropores in the porous carbon and the higher the resistivity.

[0126] Compared with the test results of Examples 1-6, the conductivity of Comparative Example 1 is poor, and the charging capacity and the first coulomb efficiency of the prepared battery are significantly reduced. This is because the β component has good coking performance during the second carbonization, the pore wall is strong, the product strength is high, and the resistivity is low, while the β component content in Comparative Example 1 is low and the γ component is more, so a porous carbon with a larger pore size and poorer conductivity is obtained. Among them, the pore size is too large, the resistance of the powder material is large, which is not conducive to lithium ion storage, reversible cycle and rate performance. Therefore, the charging capacity of Comparative Example 1 is small, the first efficiency is reduced, and the rate is low.

[0127] Compared with the test results of Examples 1-6, the pore size of Comparative Example 2 is relatively large, the pore volume and specific surface are very small, and the resistivity and charging capacity are very low. This is because no KOH was added to mix and form pores in Comparative Example 2, and the voids were not developed, resulting in a very small charging capacity. However, due to the small specific surface area, it is not easy to cause lithium eating, and the active lithium loss caused by SEI will also be reduced, so its initial efficiency is higher. The porosity is low, that is to say, the overall connection inside the material is relatively complete, and there are not too many pores to divide the material, that is, there are more conductive paths, so the resistance is lower and the magnification is relatively good.

Claims

1. A method for preparing a pitch-based porous carbon material, characterized in that: It includes the following steps: S1, mixing a modulated asphalt with an alkali and heating it for preheating to obtain a first precursor; the modulated asphalt comprises 20-40wt% of an α component, 20-60wt% of a β component and 10-50wt% of a γ component; S2, continuing to heat the first precursor to perform a first carbonization to obtain a second precursor; S3. Continue to heat the second precursor to perform a second carbonization to obtain a pitch-based porous carbon material.

2. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: It satisfies one or more of the following conditions (1)-(6): (1) Before step S1, the step also includes step S0, mixing the asphalt raw material with the wash oil to obtain a modulated asphalt; preferably, step S0 satisfies one or more of the following conditions ac: a. The softening point of the asphalt raw material is 55-150°C, preferably 100-120°C, for example 105°C; b. The asphalt raw material comprises: 20-50wt% of the α component, 10-60wt% of the β component, and 5-70wt% of the γ component, for example, 32wt% of the α component, 58wt% of the β component and 10wt% of the γ component, where wt% refers to the mass proportion of a substance in the mixture; c. The mass ratio of the asphalt raw material to the wash oil is (0.5-6):1, for example, 1.2:1, 0.5:1, 4:1; (2) The softening point of the modulated asphalt is 80-120°C, for example, 95°C; (3) The average relative molecular mass of the modulated asphalt is 1000-1800, for example, 1000, 1400, 1800; (4) The modulated asphalt contains 30 wt% of the α component, 38 wt% of the β component, and 32 wt% of the γ component; or, the modulated asphalt contains 29 wt% of the α component, 27 wt% of the β component, and 44 wt% of the γ component; or, the modulated asphalt contains 31 wt% of the α component, 49 wt% of the β component, and 20 wt% of the γ component; (5) The C / H of the prepared asphalt is 1.25-2.0, preferably 1.35-1.85, such as 1.48, 1.57, 1.35; (6) The prepared asphalt is in granular form, and the D 50 6-18 μm, preferably 8-12 μm, for example 10 μm.

3. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions ae: a. The base is one or more of potassium hydroxide, potassium carbonate, potassium chloride, sodium carbonate, sodium chloride, zinc chloride, zinc carbonate and phosphoric acid, for example potassium hydroxide; b. The mass ratio of the modulated asphalt to the alkali is 1:(1-5), for example 1:1 or 1:4; c. The heating temperature is 90-140°C, preferably 110-130°C, for example 125°C; d. The heating rate is 0.5-20°C / min, for example 2°C / min; e. The specific steps of the pre-heating are: heating the powder obtained by mixing the above-mentioned modulated asphalt and alkali to the heating temperature and then keeping it warm to ensure that the asphalt is completely melted into liquid, and then introducing a non-reactive gas, wherein the non-reactive gas is one or more of nitrogen, helium and argon; the gas flow rate of the non-reactive gas is preferably 0.05-60L / min, more preferably 0.05-1L / min, for example 0.2L / min; the insulation time is preferably 0.2-2h, more preferably 0.5-1.5h, for example 30min.

4. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: Step S2 satisfies one or more of the following conditions ac: a. The temperature of the first carbonization is 200-600°C, preferably 400-500°C, for example 450°C; b. The heating rate is 0.5-20°C / min, for example 3°C / min c. The specific steps of the first carbonization are: introducing a non-reactive gas into the first precursor on the basis of the pre-heating temperature, continuing to heat up to the temperature of the first carbonization and keeping the temperature; wherein the non-reactive gas is preferably one or more of nitrogen, helium and argon; wherein the gas flow rate of the non-reactive gas is preferably 0.05-60L / min, for example 0.2L / min; wherein the insulation time is preferably 1-6h, for example 1h.

5. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: It satisfies one or more of the following conditions (1)-(5): (1) The temperature of the second carbonization is 600-1400° C., for example, 700° C., 1000° C. or 1300° C.; (2) The second carbonization time is 2-8 hours, for example 2 hours, 4 hours or 7 hours; (3) In step S2, the heating rate is 0.5-20°C / min, preferably 1-10°C / min, for example 5°C / min; (4) The specific steps of the second carbonization in step S3 are: maintaining a non-reactive gas atmosphere, continuing to heat to the temperature of the second carbonization and keeping the temperature, cooling to room temperature after keeping the temperature, taking out, acid washing 3 times, washing with water 3 times, and then drying; preferably, step S3 satisfies one or more of the following conditions ac: a. The non-reactive gas is one or more of nitrogen, helium and argon; b. The gas flow rate of the non-reactive gas is 0.05-60 L / min, for example 0.15 L / min; c. The acidic solution used for pickling is one or more of hydrochloric acid solution, phosphoric acid solution, nitric acid solution, sulfuric acid solution, acetic acid solution, and formic acid solution, such as hydrochloric acid solution; wherein the concentration of the acidic solution is preferably 0.5-6 mol / L, such as 3 mol / L; wherein the stirring time of the pickling is preferably 1-10 h, more preferably 2-5 h, such as 3 h; (5) After step S3, the method further includes step S4, spheroidizing the porous carbon material; the spheroidizing time is preferably 10-60 min, for example, 30 min; the spheroidizing is preferably performed in a shaping machine, and the rotation speed of the shaping machine is preferably 20-70 rpm, for example, 50 rpm; the D of the porous carbon material after the spheroidizing is 50 It is preferably 3-20 μm, for example 7-8 μm.

6. A pitch-based porous carbon material precursor, characterized in that: The asphalt-based porous carbon material precursor is prepared by the following steps S1: S1. Mixing the modulated asphalt with alkali and heating it for preheating to obtain an asphalt-based porous carbon material precursor; the modulated asphalt contains 20-40wt% of the α component, 20-60wt% of the β component and 10-50wt% of the γ component; wherein the conditions and operations of step S1 are as described in any one of claims 1-3; Alternatively, the asphalt-based porous carbon material precursor is prepared by the following steps S1-S2: S1, mixing a modulated asphalt with an alkali and heating it for preheating to obtain a first precursor; the modulated asphalt comprises 20-40wt% of an α component, 20-60wt% of a β component and 10-50wt% of a γ component; S2. Continue to heat the first precursor to perform a first carbonization to obtain a pitch-based porous carbon material precursor, wherein the conditions and operation of step S1 are as described in any one of claims 1-3, and the conditions and operation of step S2 are as described in any one of claims 1, 4-5.

7. A pitch-based porous carbon material prepared by the method for preparing a pitch-based porous carbon material according to any one of claims 1 to 6.

8. The pitch-based porous carbon material according to claim 7, characterized in that: The pitch-based porous carbon material satisfies one or more of the following conditions ad: a. The specific surface area of ​​the asphalt-based porous carbon material is 900-2500m 2 / g, preferably 1000-1800m 2 / g, for example 1123m 2 / g, 1543m 2 / g, 1641m 2 / g; b. The pore size D of the pitch-based porous carbon material 50 1-15 nm, for example, 2.146 nm, 3.176 nm, 3.209 nm, 3.653 nm, 4.641 nm, 5.278 nm, 9.017 nm or 14.45 nm; c. The pore volume of the asphalt-based porous carbon material is 0.5-1.3cm 3 / g, for example, 0.6436cm 3 / g, 0.6936cm 3 / g, 0.764cm 3 / g, 0.8987cm 3 / g, 0.9254cm 3 / g, 0.9423cm 3 / g, 1.034cm 3 / g or 1.278cm 3 / g; d. The powder resistivity of the pitch-based porous carbon material at 20 MPa is 0.04-0.16 Ω*cm, for example, 0.0498 Ω*cm, 0.0577 Ω*cm, 0.0752 Ω*cm, 0.0818 Ω*cm, 0.0824 Ω*cm, 0.1023 Ω*cm, 0.1176 Ω*cm or 0.1578 Ω*cm.

9. Use of the pitch-based porous carbon material according to claim 7 or 8 as an electrode material.

10. A battery, characterized in that: It comprises the pitch-based porous carbon material according to claim 7 or 8.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon negative electrode material

    CN116314791A

  • Nitrogen-doped silicon-carbon negative electrode material and preparation method thereof

    CN117410466A

  • Composite carbon-silicon negative electrode material and preparation method thereof

    CN117577801A

  • Composite asphalt-based active carbon preparation method and supercapacitor

    CN106115694A

  • Porous carbon as well as preparation method and application thereof

    CN113603078A

Cited By

  • Preparation method of waste asphalt carbon with microcrystalline vortex structure as ion battery material

    CN120229705A

  • Preparation method of pitch-based porous carbon for high-performance silicon carbon

    CN120922872A

  • A method for preparing pitch-based porous carbon for high-performance silicon-carbon applications

    CN120922872B